Aflatoxin in feedstuffs and raw milk in Republic of North Macedonia, occurrence and assessment - SANTA, DUSHICA; SRBINOVSKA, SONJA; GJORGJIEVSKI, SREKJKO; GRUEVSKA, VIKTORIJA; ARSOVSKA, FROSINA (Digital ProScholar Media, 2021)
The main objective of this research is to estimate the situation of occurance of aflatoxins in feedstuffs and aflatoxin M1 raw cow`s milk in Republic of North Macedonia. Detected average concentrations of total aflatoxins in the examined period 2014-2017 were below legal prescribed level. Within the official monitoring programme in the country, 1718 samples of raw cow's milk have been analyzed during 2017 and 2018. Comparison of the data showed that the number of examined samples with values for aflatoxin M1 above the allowed limits, according to the regulation is in 2018 (10 samples) and 2017 (5 samples). Additionally, the calculation of exposure assessment of the human population in North Macedonia demonstrated that the exposure to AFM1 of the adult population in N. Macedonia for 2017 is 0.0563 ng/kg bw/daily, and for 2018 is 0.0824 ng/kg bw/daily. The calculated hazard index (HI) In both years, was lower than one, which means that there are no significant health risks for the consumers. It is important to have continuously low levels of aflatoxins in animal feed and nutrition, especially that the climate changes create more favorable conditions for the development of moulds of Aspergillus.